A practical guide to teaching physical education in the secondary school - Capel, Susan Anne, 1953-; Cliffe, Joanne; Lawrence, Julia Clare (London : Routledge, 2020)
A Practical Guide to Teaching Physical Education in the Secondary School is written for all student teachers on university and school-based initial teacher education programmes. It offers a wealth of tried and tested strategies together with practical activities and materials to support your teaching to enhance pupils' learning. It is designed for you to dip in and out of, and enable you to focus on specific areas of teaching, your programme or pupils' learning. This third edition is fully updated with the most recent developments inteaching physical educationand features five brand new chapters. Key topics covered include: Planning schemes of work, units of work and lessons Safe practice, risk assessment and risk management Promoting positive behaviour Applying theories of learning to your practice Overcoming barriers and maximising the achievement of all pupils Assessing learning Physical literacy NEW Health related learning NEW Using digital technologies NEW Reflective practice and action research Managing your workload, resilience, health and well-being NEW Working with your mentor NEW Photocopiable resources offer assistance in lesson observation, planning, preparation, teaching and evaluation. An annotated 'Further resources' section at the end of each chapter provides information about some usefuladditional resources to support you in your development as a teacher. Illustrated throughout with examples of existing good practice, this highly practical resource offers valuable support and guidance to all student teachers as well as those in the early years of their teaching career. Although A Practical Guide to Teaching Physical Education in the Secondary School, 3rd Edition can be used successfully on its own, it is alsoa companion to Learning to Teach Physical Education in the Secondary School, 5th Edition and can be used to reinforce the basic teaching skills covered in that core textbook.
OCLC-licensed vendor bibliographic record.
Keywords: Physical education and training -- Study and teaching (Secondary); Physical education and training -- Curricula; EDUCATION / General